EVALUASI ERGONOMI DENGAN PENDEKATAN FISIOLOGI DAN PENILAIAN POTENSI RESIKO CIDERA DENGAN METODE QUICK EXPOSURE CHECK PADA BURUH GENDONG WANITA - Parwati, Cyrilla Indri; Simanjuntak, Risma Adelina (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
â€œBuruh Gendongâ€ women in Bringharjo market Yogyakarta, still carry loads on their back physically and use manual big basket and shawl. When they carry loads on their back unnaturally, their body postures are too hunchbacked, their heads are bent down and their arms are up-and-down, etc. The performance of the women is not so ergonomic that can makes them have injury. Therefore, it is important to evaluate how to minimize the risk of work accident. Ergonomic evaluation with physiology approach and Quick Exposure Check Method are the methods that can know how much the loads of the labor is and how many risk of injury by evaluating pulse and body posture when they work. Based on the research of â€œburuh gendongâ€, it can be obtained (1) load that was carried on back by the labor around 50 â€“ 100 kgs. It means that the load is overstep than load limit suggested load limit around 10-16 kgs, (2) work load classification based on pulse is high work load, (3) means of energy needed by the labor is 5.15182 kcal/minutes that is overstep standard 4 kcal/minutes, (4) total score of observer is 162 and total score of worker evaluation is 26 are classified as action level 4 which evaluation observed and changed at that time. The conclusion of this research is that â€œburuh gendongâ€ women working in Bringharjo market tends to have injury risk. Therefore, it is suggested to design ergonomic work system by considering characteristics of work, worker, material, and work management.